Research progress on thermochemical conversion technology of sewage sludge - ZOU Zhengkang; GUO Xiao; LIANG Sha*; XU Xiaoxiao; DUAN Huabo; YANG Jiakuan (能源环境保护)
China′s urbanization level is continuing to rise, and the annual production of municipal sludge has exceeded 70 million tons. In addition to organic components and nutrients, municipal sludge may also contain pollutants such as pathogenic bacteria and heavy metals, which pose potential environmental risks. With the annual growth of sludge production, treating and disposing of sludge has become a prominent problem in realizing the construction of a " waste free city" . In recent years, with the deepening research and development of sludge thermochemical conversion technology, it has shown great application potential for sludge treatment and disposal. This paper reviews the research and demonstration application progress of typical sludge thermochemical conversion technologies, and focuses on the latest research achievements in the basic characteristics, influential parameters, product compositions, and resource utilization pathways of thermochemical conversion technologies such as sludge incineration, pyrolysis, gasification, and hydrothermal treatment. Additionally, the paper summarizes the research and application progress of collaborative disposal of sludge with other organic solid wastes. Furthermore, the carbon emission intensity and level of different sludge thermochemical conversion technologies and their calculation methods are summarized and analyzed. On this basis, an outlook on the future research directions of sludge thermochemical conversion technology is proposed, aiming to provide reference for the selection and optimization of sludge treatment and disposal methods.